The Effectiveness of the PhET-Assisted Creative Problem Solving Model on Students' Creative Thinking Abilities and Cognitive Learning Outcomes - Yani, Liyana Putri; Widiyatmoko, Arif (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This research aims to determine the effectiveness of the PhET-assisted creative problem solving model on creative thinking abilities and student learning outcomes in vibration, wave and sound materials. In this research, the samples taken were determined based on the characteristics of the two classes which were almost the same (homogeneous). The characteristics used are the average UAS scores of two classes which are close to the same and the science teacher who teaches in the same class. The sample chosen was class VIII with class A as the control class and class B as the experimental class with a total of 16 students in each class. This research uses an experimental method with a nonequivalent control group design. Data on students' cognitive learning outcomes were taken using a test method in the form of 15 multiple choice questions, while students' creative thinking abilities used a test method in the form of 5 descriptive questions which had been tested for validity and reliability with a significance level of 5%, resulting in rcount > rtable. Research data was obtained from pretest-posttest scores and analyzed using the MANCOVA statistical test. The results of the multivariate analysis show that the sig value is <0.05, namely 0.001 <0.005, which means that there is a significant influence. The N-gain results show an increase in creative thinking abilities by 56.57% and an increase in students' cognitive learning outcomes by 57.08% which is included in the medium category. Therefore, it can be concluded that the use of the creative problem solving model assisted by PhET significantly increases students' creative thinking abilities compared to conventional learning. In addition, there is a significant increase in the cognitive learning outcomes of students who use this model. The implementation of PhET as an interactive learning tool opens up opportunities for students to understand science concepts in a more in-depth and contextual way. Implications of these findings include increased student engagement, development of innovative learning models, and emphasis on problem-based learning. This research contributes to educational practitioners and researchers in understanding the potential of the PhET-assisted creative problem solving model as a practical approach to improving students' learning outcomes and creative thinking abilities in the context of science learning.